Perkembangan Nagham di Indonesia: Sejarah dan Diskursus Implementasinya - Ikhwan, Masrur (STAI Darul Kamal NW Kembang Kerang, 2024)
This article aims to analyze the development of Nagham in Indonesia by taking the historical context and discourse on its implementation. This study is more popularly known as style, even though the essence of the object is the same, namely about the melody or rhythm of reading the Al-Qur'an. This article uses a qualitative method by explaining it descriptively-analytically from document data. This article finds that the development of nagham in Indonesia cannot be separated from the articulation of the command to read the Al-Qur'an in a beautiful voice. Beauty itself is born from elements of art that are related to beauty and communal culture. As for the history in Indonesia, the development of this science also received support from the government through MTQ activities, universities that concentrate on this science such as PTIQ, IIQ, and others. Meanwhile, the implementation discourse is still being debated regarding the use of non-Arabic styles. Although this debate will gradually reach its own meeting point. This article also provides input related to government policy in accommodating Nagham developments for official events such as MTQ, etc. Without interfering with majority-minority views, because that is part of the development of the art of reading the Al-Qur'an.